Penerapan Strategi ‘Ada Tawa Ceria’ Dan Media Film Pendek Dalam Pembelajaran Menulis Teks Narasi Peserta Didik Kelas VII SMPN 25 Semarang 2022/2023 - Wiwin Kurnia; Eva Ardiana Indrariani; Rawinda Fitrotul Mualafina (CV. Alim's Publishing, 2024)
This research was motivated by the writing ability of class VII participants which was still not optimal. All of this is based on the fact that interest in writing is still low, difficulty in expressing ideas or ideas into narrative texts, often looking at original texts when creating stories or essays. This research aims to describe the application of the